2013
DOI: 10.1016/j.freeradbiomed.2013.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Induction of oxidative and nitrosative damage leads to cerebrovascular inflammation in an animal model of mild traumatic brain injury induced by primary blast

Abstract: We investigate the hypothesis that oxidative damage of the cerebral vascular barrier interface (the blood brain barrier, BBB) causes the development of mild traumatic brain injury (mTBI) during primary blast wave spectrum. The underlying biochemical and cellular mechanisms of this vascular layer-structure injury are examined in a novel animal model of shock tube. We first established that low frequency (123 kPa) single or repeated shock wave causes BBB/brain injury through biochemical activation by acute mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
264
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(274 citation statements)
references
References 29 publications
10
264
0
Order By: Relevance
“…Oxidative stress and bloodbrain-barrier permeability also occur in models of blast- PERSISTENT DAMAGE AFTER EYE TRAUMAinduced TBI, suggesting a similar mechanism in the eye and brain. 20,21 Consistent with the RPE damage, levels of ROS were increased early after trauma from an eye-directed overpressure airwave. We detected increases in superoxide and peroxynitrite, in particular.…”
Section: Bricker-anthony Hines-beard and Rexmentioning
confidence: 69%
“…Oxidative stress and bloodbrain-barrier permeability also occur in models of blast- PERSISTENT DAMAGE AFTER EYE TRAUMAinduced TBI, suggesting a similar mechanism in the eye and brain. 20,21 Consistent with the RPE damage, levels of ROS were increased early after trauma from an eye-directed overpressure airwave. We detected increases in superoxide and peroxynitrite, in particular.…”
Section: Bricker-anthony Hines-beard and Rexmentioning
confidence: 69%
“…Upregulation of MMP-2 seemed to be happened in shorter duration compared to MMP-9. Abdul-Muneer et al (2013) reported that MMP-2 level would significantly decrease after 6 hours, unlike MMP-9 that persistently increased in first 24 hours 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Blast-induced TBI also caused oxidative damage to blood-brain barrier (BBI) associated with induction of NADPH oxidase and inducible nitric oxide synthase (iNOS) both of which increase the production of free radicals (Kochanek et al, 2013). Cerebral vascular injury occurred prior to the development of neurological deficits in mild TBI and was accompanied by the activation of caspase-3 and apoptosis in the perivascular region around the lesion (Abdul-Muneer et al, 2013). In transgenic mouse model of Alzheimer's disease amyloidosis using Tg2576 mice, repetitive concussive brain injury induced by a modified cortical impact model of closed head injury increased the levels of brain lipid peroxidation, accelerated beta amyloid deposition, and caused learning deficits.…”
Section: Oxidative Stress In Mild Tbimentioning
confidence: 99%